2023
DOI: 10.1007/s10120-023-01372-7
|View full text |Cite
|
Sign up to set email alerts
|

Quality-adjusted time without symptoms or toxicity analysis of nivolumab plus chemotherapy versus chemotherapy alone for the management of previously untreated patients with advanced gastric cancer, gastroesophageal junction cancer, or esophageal adenocarcinoma

Abstract: Background The phase 3 CheckMate 649 established superior overall survival of nivolumab in combination with chemotherapy (NIVO + chemo) compared with chemotherapy (chemo) alone as a first-line treatment for patients with Her2-negative advanced gastric cancer, gastroesophageal junction cancer, and esophageal adenocarcinoma (GC/GEJC/EAC). This post hoc trial analysis aimed to evaluate the benefit of NIVO + chemo using quality-adjusted time without symptoms or toxicity (Q-TWiST) to further account f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Different chemotherapy regimens may have varying degrees of synergistic or additive effects when combined with nivolumab. Fourth, this study did not analyze patient-reported outcomes [ 1 ] or quality-adjusted survival [ 30 ], which are important considerations in the evaluation of cancer treatments. Since our study is a study containing real-life data, it does not include a control arm like other similar real-life studies in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Different chemotherapy regimens may have varying degrees of synergistic or additive effects when combined with nivolumab. Fourth, this study did not analyze patient-reported outcomes [ 1 ] or quality-adjusted survival [ 30 ], which are important considerations in the evaluation of cancer treatments. Since our study is a study containing real-life data, it does not include a control arm like other similar real-life studies in the literature.…”
Section: Discussionmentioning
confidence: 99%